Thirst: The Shadow of Death - Pike, Christopher (Simons & Schuster UK Ltd, 2011)
The ability to adapt has been the key to Alisa's survival through the centuries. Now, once more, she finds that her life depends on that very transformation. But Alisa will soon learn, change isn't always good...
Keywords: Fiction-Horror